Neurobiological Correlates of Fatherhood During the Postpartum Period: A Scoping Review - Sobral, Mónica; Pacheco, Francisca; Perry, Beatriz; Antunes, Joana; Martins, Sara; Guiomar, Raquel; Soares, Isabel; Sampaio, Adriana; Mesquita, Ana; Ganho-Ávila, Ana (Frontiers in Psychology, 2022)
During the postpartum period, the paternal brain suffers extensive and complex neurobiological alterations, through the experience of father-infant interactions. Although the impact of such experience in the mother has been increasingly studied over the past years, less is known about the neurobiological correlates of fatherhood – that is, the alterations in the brain and other physiological systems associated with the experience of fatherhood. With the present study, we aimed to perform a scoping review of the available literature on the genetic, neuroendocrine, and brain correlates of fatherhood and identify the main gaps in the current knowledge. PubMed, Scopus, and Web of Science electronic databases were searched for eligible studies on paternal neuroplasticity during the postpartum period, over the past 15 years. Reference lists of relevant key studies and reviews were also hand-searched. The research team independently screened the identified studies based on the established inclusion criteria. Extracted data were analyzed using tables and descriptive synthesis. Among the 29 studies that met our inclusion criteria, the vast majority pertained to neuroendocrine correlates of fatherhood (n = 19), followed by brain activity or connectivity (n = 7), association studies of candidate genes (n = 2), and brain structure correlates (n = 1). Collectively, studies published during the past fifteen years suggest the existence of significant endocrine (testosterone, oxytocin, prolactin, and cortisol levels) and neurofunctional alterations (changed activity in several brain networks related to empathy and approach motivation, emotional processing and mentalizing, emotion regulation, dorsal attention, and default mode networks) as a result of fatherhood, as well as preliminary evidence of genetic variability accounting for individual differences during the postpartum period in fathers. No studies were so far published evaluating epigenetic mechanisms associated with the paternal brain, something that was also the focus of the current review. We highlight the need for further research that examines neuroplasticity during the experience of fatherhood and that considers both the interplay between hormones and simultaneous assessment of the different biomarkers (e.g., associations between hormones and neural activity); data collection protocols and assessment times should also be refined.